Formulation and Evaluation of a Bromelain-Loaded Nanoemulgel for Effective Acne Treatment - Patil, Archana S; Ugare, Pratik; Patil, Arpana; Patil, Sheetal; Masareddy, Rajashree (Indian Journal of Pharmaceutical Education and Research)
Aim: This study aimed to design, optimize, and evaluate a bromelain-infused nanoemulgel to enhance its transdermal delivery and improve therapeutic outcomes in the management of Acne vulgaris. Background: Acne vulgaris remains a prevalent dermatological condition that necessitates more effective treatment strategies. Bromelain, a proteolytic enzyme, offers significant potential for acne management but is hindered by challenges such as poor aqueous solubility, limited skin penetration, and extensive first-pass metabolism. Materials and Methods: Nanoemulsions were formulated utilizing pseudo-ternary phase diagrams and optimized through a 32 factorial design. The most promising formulation, characterized by high drug content (87.55%) and a minimal globule size (105.8 nm), was incorporated into a xanthan gum-based gel matrix. Penetration enhancers, including propylene glycol, were integrated to facilitate enhanced skin absorption. The bromelain-loaded nanoemulgel was evaluated for homogeneity, pH, viscosity, extrudability, in vitro drug release and ex vivo skin permeation using rat abdominal skin. Results: The nanoemulgel demonstrated superior drug release and skin permeation compared to both emulgel and plain gel formulations. The synergistic effects of the surfactant and co-surfactant blend in the nanoemulsion significantly enhanced the delivery and penetration of bromelain, thus improving its therapeutic efficacy for Acne vulgaris. Conclusion: The bromelain-loaded nanoemulgel exhibited promising results in terms of both drug release and transdermal penetration, indicating its feasibility as an effective topical formulation for acne management. Further clinical trials are warranted to assess its efficacy and safety for broader clinical application.
Keywords: Anti-microbial study; Bromelain; Nanoemulsion; Propionibacterium acnes